ФОРМИРОВАНИЕ МЕХАНИЗМА РЕАЛИЗАЦИИ СОЦИАЛЬНОЙ ФУНКЦИИ РЫНКА БАНКОВСКИХ УСЛУГ (Journal of Economic Research & Business Administration, 2015)
Considered direction on this issue ultimately will help the general improvement of economic situation, both in financial and social, as well as provide some positive influence on the normalization of economic life and development of social infrastructure.